2019
DOI: 10.1111/gcbb.12588
|View full text |Cite
|
Sign up to set email alerts
|

Winter hardiness of Miscanthus (I): Overwintering ability and yield of new Miscanthus ×giganteus genotypes in Illinois and Arkansas

Abstract: Miscanthus ×giganteus (M×g) is an important bioenergy feedstock crop. However, biomass production of Miscanthus has been largely limited to one sterile triploid cultivar, M×g ‘1993‐1780’, which we demonstrate can have insufficient overwintering ability in temperate regions with cold winters. Key objectives for Miscanthus breeding include greater biomass yield and better adaptation to different production environments than M×g ‘1993‐1780’. In this study, we evaluated 13 M×g genotypes, including ‘1993‐1780’, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
4
28
1
Order By: Relevance
“…Although all mature plants of the commercial check, M×g '1993-1780', survived the 2013-2014 winter in this study at Urbana, IL, hardiness, and vigor scores from May and June 2014 indicated that the plants were damaged but appeared to subsequently recover by late spring. In contrast to the survival of mature M×g '1993-1780' plants in this study, in a parallel study of first year M×g '1993-1780' plants, we observed losses of 29% during the 2013-2014 winter at Urbana, IL (Dong, Green, et al, 2018). Previous studies have estimated the temperature at which 50% of isolated rhizomes from mature plants were killed (LT 50 ) for M×g '1993-1780' to be −2.6°C (Fonteyne et al, 2016), −3.4°C (Clifton-Brown & Lewandowski, 2000), or −4.4°C (Peixoto et al, 2015), but in the field, insulation of belowground rhizomes from the plant's aboveground crown, and avoidance of cold by rhizomes that grow deep in the soil, can increase overwintering ability of mature plants.…”
Section: Comparison Between This Study and Prior Studies For Wintercontrasting
confidence: 98%
See 1 more Smart Citation
“…Although all mature plants of the commercial check, M×g '1993-1780', survived the 2013-2014 winter in this study at Urbana, IL, hardiness, and vigor scores from May and June 2014 indicated that the plants were damaged but appeared to subsequently recover by late spring. In contrast to the survival of mature M×g '1993-1780' plants in this study, in a parallel study of first year M×g '1993-1780' plants, we observed losses of 29% during the 2013-2014 winter at Urbana, IL (Dong, Green, et al, 2018). Previous studies have estimated the temperature at which 50% of isolated rhizomes from mature plants were killed (LT 50 ) for M×g '1993-1780' to be −2.6°C (Fonteyne et al, 2016), −3.4°C (Clifton-Brown & Lewandowski, 2000), or −4.4°C (Peixoto et al, 2015), but in the field, insulation of belowground rhizomes from the plant's aboveground crown, and avoidance of cold by rhizomes that grow deep in the soil, can increase overwintering ability of mature plants.…”
Section: Comparison Between This Study and Prior Studies For Wintercontrasting
confidence: 98%
“…‘Illinois’), accounts for nearly all Miscanthus biomass production in North America and Europe (Clifton‐Brown, Chiang, & Hodkinson, ; Clifton‐Brown & Lewandowski, ; Clifton‐Brown, Stampfl, & Jones, ; Głowacka et al, ; Heaton, Dohleman, & Long, ; Heaton, Voigt, & Long, ; Somerville, Youngs, Taylor, Davis, & Long, ). Although M×g ‘1993‐1780’ is high‐yielding, insufficient winter hardiness can cause severe plant losses in cold temperate environments, especially during the first winter after planting, and losses in yield in mature stands (Burner, Tew, Harvey, & Belesky, ; Christian & Haase, ; Clifton‐Brown & Lewandowski, ; Clifton‐Brown et al, ; Dong, Green, et al, ; Maughan et al, ). Thus, in regions where average annual minimum temperatures are −26.1°C (USDA hardiness zone 5b; U.S. Department of Agriculture, ) or lower, inconsistent stand establishment and productivity of M×g ‘1993‐1780’ results in great economic risk that is unacceptable for commercial agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all Miscanthus biomass production currently uses a single high‐yielding clone of M . × giganteus (Głowacka et al, ), despite its insufficient winter hardiness in USDA zone 5b environments and colder (<−26.1°C average annual minimum air temperature; Dong, Green et al, ), as well as the risk of disease and pest susceptibility associated with monoculture (Ahonsi et al, ; Arnoult & Brancourt‐Hulmel, ; Bradshaw, Prasifka, Steffey, & Gray, ; Clifton‐Brown & Lewandowski, ; Prasifka et al, ). We refer to this clone as M .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the standard clone of M . × giganteus is insufficiently winter‐hardy in parts of northern Europe and northern parts of the US Midwest (Clifton‐Brown & Lewandowski, ; Dong et al, ), and it flowers too early to yield optimally at lower latitudes (~30°) such as the coastal plain of the southern United States (E. J. Sacks, unpublished data). Both M. sinensis and M. sacchariflorus are native to a broad range of environments across East Asia and should provide a wealth of breeding material for developing new biomass cultivars (Clifton‐Brown et al, ).…”
Section: Introductionmentioning
confidence: 99%